2002
DOI: 10.1023/a:1017972622312
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The effects of extracellular Mg2+ on both dynamic changes of [Ca2+]i and apoptosis rate were analysed. The consequences of spatial and temporal dynamic changes of intracellular Ca2+ on apoptosis, in thapsigargin- and the calcium-ionophore 4BrA23187-treated MCF7 cells were first determined. Both 4BrA23187 and thapsigargin induced an instant increase of intracellular Ca2+ concentrations ([Ca2+]i) which remained quite elevated (> 150 nM) and lasted for several hours. [Ca2+]i increases were equivalent in the cytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Consequently, shifting the ratio towards the magnesium would inhibit Ca influx and tumor cell proliferation. These findings were also supported by the work from Pereira et al The authors observed an inhibited chemically triggered Ca influx through the plasma membrane of MCF-7 cells in the presence of high extracellular Mg levels [ 63 ]. Normally, Ca influxes the cells following absorption to mitochondria and the endoplasmic reticulum.…”
Section: Discussionsupporting
confidence: 73%
“…Consequently, shifting the ratio towards the magnesium would inhibit Ca influx and tumor cell proliferation. These findings were also supported by the work from Pereira et al The authors observed an inhibited chemically triggered Ca influx through the plasma membrane of MCF-7 cells in the presence of high extracellular Mg levels [ 63 ]. Normally, Ca influxes the cells following absorption to mitochondria and the endoplasmic reticulum.…”
Section: Discussionsupporting
confidence: 73%
“…We identified thapsigargin to be beneficial to the apoptosis FM but broadly harmful to the signal transduction, transcription, cell proliferation, and RNA metabolic process FMs. This drug has been reported to have the ability to promote apoptosis on prostate and breast cancer cells but also to stimulate cell growth in mouse keratinocyte models (Table 1) [42][47].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments on the nucleus isolated from cells clearly demonstrate the induction of Ca 2+ -dependent endonuclease activity during triggering apoptosis events [47]. Rises in intracellular Ca 2+ concentration activates endonuclease that mediates DNA cleavages into oligonucleosome fragments [48]. Regucalcin has been shown to have an inhibitory effect on Ca 2+ -activated DNA fragmentation in isolated rat liver nucleus [41].…”
Section: Regucalcin Suppresses Apoptosis In Modeled Liver Cellsmentioning
confidence: 99%
“…Thapsigargin-induced DNA fragmentation in the hepatoma cells is not altered after culture with caspase inhibitor, suggesting that thapsigargin-mediated apoptosis is independent on activation of caspases [48]. Overexpression of regucalcin in hepatoma cells suppresses thapsigargin-induced DNA fragmentation [36].…”
Section: Regucalcin Suppresses Apoptosis In Modeled Liver Cellsmentioning
confidence: 99%